APPLYING OF THE COOPERATIVE TYPE SNOWBALL THROWING LEARNING MODEL TO IMPROVE LEARNING ACHIEVEMENT STUDENTS ABOUT DIGESTIVE ORGANS IN GRADE V SD NEGERI 012 BARRA-BARRA MAMASA REGENCY - Rasmi Djabba; Ila Israwaty; Patrycian Dagin Rara (Universitas Labuhanbatu, 2023)
The purpose of this study is to describe the applying of the type cooperative learning model Snowball Throwing in the process of learning students about the Digestive Organs in grade students SD Negeri 012 Barra-Barra Mamasa Regency and to find out the application of the type cooperative learning model Snowbal Throwing in improving learning achievement about the Digestive Organs in grade V SD Negeri 012 Barra-Barra Mamasa Regency. The focus of this research is in the of learning processes and achievement. The applying of the action was carried out for 2 cycles and each cycle consisted of 1 meeting. Data collection techniques used are observation, tests and documentation. The data analysis technique used is data condensation, data presentation, and conclusion. The subjects of this study were teachers and students in grade V, totaling 20 students. In the first cycle the results of teacher observations were in sufficient qualification (C), the results of student observations were in the sufficient qualification (C) and student learning achievement showed an average qualification (C). In the second cycle the results of teacher observations were in the good qualification (B), the results of student observations are in the good qualification (B) and student learning achievement show an average qualification (B). This shows that the process and learning achievement students in grade students V SD Negeri 012 Barra-Barra Mamasa Regency after applying the type cooperative learning model snowball throwing experienced a significant increase.Keywords: Snowball Throwing Type Cooperative Learning Model,learning achievement. AbstrakTujuan dalam penelitian ini yaitu untuk mendeskripsikan penerapan model pembelajaran kooperatif tipe Snowbal Throwing dalam proses belajar siswa tentang Organ Pencernaan di kelas V SD Negeri 012 Barra-Barra Kabupaten Mamasa dan untuk mengetahui penerapan model pembelajaran kooperatif tipe Snowbal Throwing dalam meningkatkan hasil belajar siswa tentang Organ Pencernaan di kelas V SD Negeri 012 Barra-Barra Kabupaten Mamasa. Fokus penelitian adalah proses dan hasil belajar. Pelaksanaan tindakan dilakukan selama 2 siklus dan setiap siklus terdiri 1 kali pertemuan. Teknik pengumpulan data yang digunakan adalah observasi, tes dan dokumentasi. Teknik analisis data yang digunakan yakni kondensasi data, Penyajian data, dan Penarikan kesimpulan. Subjek penelitian ini yaitu guru dan siswa kelas V yang berjumlah 20 orang. Pada siklus I hasil observasi guru berada pada kualifikasi cukup (C), hasil observasi siswa berada pada kualifikasi cukup (C) dan tes hasil belajar siswa menunjukkan dengan kualifikasi cukup (C). Pada siklus II hasil observasi guru berada pada kualifikasi baik (B), hasil observasi siswa berada pada kualifikasi baik (B) dan hasil belajar siswa menunjukkan dengan kualifikasi baik (B). Hal ini menunjukkan bahwa proses dan hasil belajar siswa di kelas V SD Negeri 012 Barra-Barra Kabupaten Mamasa setelah diterapkan model pembelajaran kooperatif tipe snowball throwing mengalami peningkatan yang signifikan.Kata kunci: Model Pembelajaran Kooperatif Tipe Snowball Throwing, Hasil belajar.